Maldives : Action Plan for PFM Reforms Based on PEFA Assessment. (IMF Staff Country Reports; Country Report ;, 2010)
This report discusses the Action Plan for Public Financial Management (PFM) Reforms Based on PEFA Assessment for the Maldives. The purpose of the action plan is to help prioritize efforts in light of scarce resources. The recently completed Public Expenditure and Financial Accountability (PEFA) assessment indicates significant weaknesses in the PFM. Budget credibility is low, although the budget is comprehensive. Budget execution, control, procurement, accounting, and reporting are weak. External audit and legislative oversight has been lacking. Improvements are under way in many areas.